Reseña de DAVENZA TILLMANNS, M. - THORNLEY, B.: Why We Are in Need of Tails - VAN SIJL, CLAARTJE (Revista Internacional de Filosofía Aplicada HASER, 2021)
Reseña de DAVENZA TILLMANNS, M. - THORNLEY, B.: Why We Are in Need of Tails